A Framework for the Analysis of Pension and Unemployment Benefit Reform in Poland - Perraudin, W. (IMF Working Papers; Working Paper ;, 1994)
This paper examines the impacts on welfare, savings, labor supply, and the government budget of several possible reforms of the Polish pension and unemployment benefit systems. The framework of analysis is a life cycle simulation model of household consumption, labor supply and retirement decisions. The paper builds on past work by Perraudin and Pujol (1992). The present study focusses on the length of averaging periods in pension benefit calculations, measures to offset incentives to early retirement, and interactions between pension and unemployment benefit systems.